„Gniew człowieka przyniesie Ci chwałę” (Ps 76,11) - Węgrzyniak, Wojciech (Verbum Vitae, 2018)
The aim of this article is to analyze Ps 76:11, one of the most difficult verses in the Bible. First, the author analyzes (1) the Hebrew manuscripts and (2) the various ancient versions of this text. He then presents (3) the opinions of different biblical scholars and also (4) the rendering of the verse in selected modern Bible translations. In the conclusion, (5) the author offers three possible interpretations without resorting to emendation of the Masoretic Text.